Effect of Fluorosis on Liver Cells of VC Deficient and Wild Type Mice. (16th February 2014) - Wei, Wei; Jiao, Yan; Ma, Yonghui; Stuart, John M.; Li, Xiudian; Zhao, Fusheng; Wang, Lishi; Sun, DianJun; Gu, Weikuan
Abstract : For decades, mouse and other rodents have been used for the study of oxidative or related studies such as the effect of fluoride. It is known that rodents normally synthesize their own vitamin C (VC) due to the presence of a key enzyme in ascorbic acid synthesis, l-gulono-lactone- γ -oxidase ( Gulo ), while humans do not have the capacity of VC synthesis due to the deletion of most parts of the GULO gene. The spontaneous fracture ( sfx ) mouse recently emerged as a model for study of VC deficiency. We investigated the effect of fluoride on liver cells from wild type Balb/c and sfx mice. We found that activities of SOD, GPx, and CAT were reduced in both wild type and sfx mice; however, the amount of reduction in the sfx cells is more than that in Balb/c cells. In addition, while both cells increased MDA, the increase in the sfx cells is greater than that in Balb/c cells. Gene networks of Sod, Gpx, and Cat in the liver of humans and mice are also different. Our study suggests that reaction to fluoride in vitamin C deficient mice might be different from that of wild type mice.